THE ANALYSIS OF COMPUTER-BASED NATIONAL EXAMINATION RESULTS IN SCIENCE SUBJECT IN KABUPATEN SOLOK - Atika Putri Wulandari; Arief Muttaqiin (Department of Science Education, 2020)
This research is a descriptive study with a qualitative approach that describes the achievement of the national computer-based exam with science subjects in junior high school in 2019 in Solok Regency. Data collection is done by the documentation method and analyzed by descriptive statistics. The findings showed that the results of the computer-based national examination with science subjects there are was in category D which is the achievement category below 50. The computer-based national examination is carried out by 48 SMP, and 3255 students participated. The score for the Sciences subject in Solok Regency is 46.15, the 16th position out of 19 districts/cities in Sumatera Barat. the average score for science subjects in the highest junior high school level was 62.35 and the lowest score was 38.44, with 7 schools getting the C category, and 41 schools with the D category.